1994
DOI: 10.1073/pnas.91.22.10422
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the transition state for the folding/unfolding of the barley chymotrypsin inhibitor 2 and its implications for mechanisms of protein folding.

Abstract: The equilibrium and kinetics of folding of the single-domain protein chy yp hibItor 2 conform to the simple two-state ode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
181
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 36 publications
16
181
0
Order By: Relevance
“…For smaller proteins, such as the chymotrypsin inhibitor 2, only one unit is generated. For larger proteins, several hydrophobic folding units are automatically obtained, and often more than one hydrophobic folding unit is generated for a domain (e.g., four units for actin), consistent with the projection that in larger proteins, formation of a domain may be preceded by a collapsed, rearranged, hydrophobic module (Otzen et al, 1994). Whereas some hydrophobic folding units are straightforwardly identified by our algorithm, others are more difficult to discern.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…For smaller proteins, such as the chymotrypsin inhibitor 2, only one unit is generated. For larger proteins, several hydrophobic folding units are automatically obtained, and often more than one hydrophobic folding unit is generated for a domain (e.g., four units for actin), consistent with the projection that in larger proteins, formation of a domain may be preceded by a collapsed, rearranged, hydrophobic module (Otzen et al, 1994). Whereas some hydrophobic folding units are straightforwardly identified by our algorithm, others are more difficult to discern.…”
supporting
confidence: 57%
“…Consequently, a native globular protein generally displays a compact structure, containing a hydrophobic interior. For the smaller proteins, this native structure has been proposed to be achieved via a two-state kinetic model Otzen et al, 1994). This, however, may not be the case for the larger proteins, where the initial fast step may involve collapse of the hydrophobic cores with subsequent rearrangement to yield some fully formed secondary structure elements along with tertiary structure interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fersht and coworkers found that specific interactions in the folding nucleus are equally important determinants of folding rates. For example, mutations in the folding nucleus of CI2 did not change its contact order, but result in a three order magnitude increase in the folding rate [90,121,122]. Sequence-based prediction of folding rates has also been proposed and was found to be of comparable performance to that of contact order [123,124].…”
Section: Protein Folding Kineticsmentioning
confidence: 99%
“…CI2 transition state has secondary, tertiary structure elements [121]. Native topology and hydrogen bonds mediates SH3 folding [250,251].…”
Section: Mechanism Of Folding/ Unfoldingmentioning
confidence: 99%